Virtual reality system development designed for optimization of athletes` psychophysiological state - Igolkina, A. E.; Mitin, I. N.; Nazarov, K. S.; Zholinsky, A. V.; Kravchuk, D. A.; Ogannisyan, M. G.; Feshchenko, V. S.; Avdyukhanov, R. K.; Vatslon, S. A.; Mitin, A. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The purpose of the study was to produce a prototype of a hardware and software complex, uniting biofeedback technology and virtual reality in a single environment. For a number of sport disciplines, we developed a library of scripts modeling precompetition conditions and competitive playground. Also, with the help of 3D modeling tools, universal objects with the ability of further specialization of content for a specific discipline were designed.